2010
DOI: 10.1016/j.anai.2010.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Development of a nomogram for identification of asthma among adults in epidemiologic studies

Abstract: IntroductionAsthma is a serious health problem with increased prevalence and incidence over recent decades in both children and adults. Identification of study subjects likely to have asthma is a key step in asthma investigations. Epidemiologic investigations have utilized questionnaires to determine asthma prevalence. [1][2][3][4][5][6] Currently there is no universally accepted standard definition of asthma for case identification in adult studies of asthma. It is essential to develop predictive models to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Nomograms are widely used as the prognostic devices in oncology [ 16 , 17 ]. In respiratory medicine, nomograms have been used to predict survival in patients with non-small cell lung cancer [ 33 ] or probability of asthma diagnosis [ 34 ]; however, we are the first to build a nomogram that predicts in-hospital mortality in patients with asthma exacerbation. Previous studies that have identified the risk factors associated with death in patients with asthma fail to identify the means of predicting the probability of death in individual patients.…”
Section: Discussionmentioning
confidence: 99%
“…Nomograms are widely used as the prognostic devices in oncology [ 16 , 17 ]. In respiratory medicine, nomograms have been used to predict survival in patients with non-small cell lung cancer [ 33 ] or probability of asthma diagnosis [ 34 ]; however, we are the first to build a nomogram that predicts in-hospital mortality in patients with asthma exacerbation. Previous studies that have identified the risk factors associated with death in patients with asthma fail to identify the means of predicting the probability of death in individual patients.…”
Section: Discussionmentioning
confidence: 99%
“…It could be more easily applied than a more time‐consuming PAQLQ in a field investigation and also in clinical practice. Although several algorithms for asthma diagnosis and for predicted PEFR have been previously developed, our PACQoL nomogram could improve the overall clinical assessment of asthma control by physicians, responding to the need of guidelines recommendation.…”
Section: Discussionmentioning
confidence: 99%
“…It could be more easily applied than a more time-consuming PAQLQ in a field investigation and also in clinical practice. Although several algorithms for asthma diagnosis (30) and for predicted PEFR (13) have been Beside the advantage of the nomogram derivation, several potential limitations need to be considered in this study. First, variables were obtained from children aged between 5 and 11 years; therefore, the nomogram may not be generalizable to older individuals and requires validation in other groups of asthmatic children.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies have developed several prediction models for the diagnosis of asthma, 28 , 29 , 30 , 31 , 32 we established an online nomogram which is more convenient for clinicians to evaluate the individual probability of asthma attack. Clinicians could access the website directly through their computer or phone, and input the information of patients to predict the risk of asthma attack, which would greatly facilitate the clinical use.…”
Section: Discussionmentioning
confidence: 99%